2020
DOI: 10.3390/ijerph17124527
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Green Design as Workplace Innovation to Relieve Service Employee Stress in the Luxury Hotel Sector

Abstract: This study is an empirical endeavor to provide a clear comprehension regarding how hotel green design as a workplace innovation contributes to relieving employee stress and emotional fatigue and improves job satisfaction and involvement in the formation of organizational citizenship behavior. A quantitative process was employed to attain the research goal. Our empirical findings demonstrated that a green design as a workplace innovation boosts the stress resilience that leads to the decreased emotional exhaust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…The magnitude of this effect is 0.351, indicating that a unit increase in emotional satisfaction as much as 0.35 increases green citizenship behavior. The results of the fourth hypothesis confirmed are consistent with studies by (Gupta, 2012;Han, 2020). In their studies, they also found a direct relationship between emotional satisfaction and green behavior in customers.…”
Section: Discussionsupporting
confidence: 90%
“…The magnitude of this effect is 0.351, indicating that a unit increase in emotional satisfaction as much as 0.35 increases green citizenship behavior. The results of the fourth hypothesis confirmed are consistent with studies by (Gupta, 2012;Han, 2020). In their studies, they also found a direct relationship between emotional satisfaction and green behavior in customers.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, 54.18% of respondents see the construction of tourist complexes with the necessary services as a way to develop tourism in the post-COVID-19 period. These new constructions featuring green design based on ecological design is a crucial factor in improving stress resilience and reducing anxiety of tourists and workers in the tourism industry [41]. The challenge is to take measures to adapt the new tourist structures to grant more protection for forms of mobility and similar crises also having a negative aspect linked to the time it takes for tourists to regain their former mobility even after the end of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Discovering the nexus between resilience and OCB is imperative given the significant impact of OCB on organizational effectiveness (Sadeghi et al, 2016). Additionally, understanding the relationship between resilience and OCB may also shed more light on maintaining employees' motivational levels to engage in extra-role activities even in the face of harsh conditions (Han et al, 2020). Therefore, this study is embarked on to fulfill this gap in extant research.…”
Section: Introductionmentioning
confidence: 99%